Estimation of the profit impact on the incumbent postal operators for different scenarios of leberalisation - Průša, Petr; Švadlenka, Libor (Univerzita Pardubice, 2004)
The paper give one from possible way of kvantification stroke of liberalization postal sector on current postal operator. With respect to lack relevant information is analyse sight on current postal operator in frames EU. By obtaining needed data would be possible apply also on postal sector CR. From those analyses is evident, that European commission passing successive liberalization of postal sector EU would have not peril current postal operator dealt incidence onwards takings growth and dealt incidence going takings advantage of current national postal operators on competition.
Keywords: poštovní služby; liberalizace; Česká Republika; Evropská Unie